Extraskeletal osteosarcoma in the urethra of a male neutered: a case report - Liza Maria Mulder; Allan Beenakkers; Camille De Ley; Sofie Maes; Marianne De Ridder; Sarah van Rijn (Acta Veterinaria Scandinavica)
Abstract Background This report describes a case of extraskeletal osteosarcoma in the proximal urethra of a male neutered cat, highlighting the associated clinical challenges. Case presentation A 9-year-old male neutered domestic shorthair cat presented to the referring veterinarian with symptoms of stranguria, dysuria, and haematuria. Following abdominal radiographs, the cat was referred to a specialty centre for abdominal ultrasound and surgical intervention. During an exploratory laparotomy aimed at removing a suspected urolith, it became clear that the removal was not feasible, leading to the decision to euthanize the cat while still under anaesthesia. Histopathological examination of the urinary bladder and urethra confirmed the presence of an osteosarcoma in the urethra. Conclusions While extraskeletal osteosarcoma has been documented in cats, there are no known reports specifically detailing osteosarcomas of the urethra and bladder in this species. When cats present with stranguria and dysuria, and the diagnosis is not evidently an urolith, osteosarcoma should be considered among the differential diagnoses. Further diagnostic imaging, such as a CT scan, may be warranted to ensure accurate diagnosis and appropriate management.